Applications of Aluminium and Concrete Composite Structures. (2015) - Szumigała, Maciej; Polus, Łukasz
Abstract: The paper presents exemplary applications of aluminium and concrete composite structures. It discusses arguments for using these structures and reasons why in some cases it is advisable to replace a steel beam with an aluminium beam. Additionally, the article aims at analysing aluminium and concrete structures as a part of sustainable development. To this end, an analysis of materials used in aluminium and concrete composite structures was conducted. Moreover, the article presents a new method of joining an aluminium beam and a concrete slab, which may have a practical application.